Operation experience of LION and RHIC-EBIS for RHIC and NSRL. Issue 1 (1st April 2022) - Kanesue, T.; Beebe, E.; Coe, B.; Ikeda, S.; Kondrashev, S.; Lopez-Reyes, A.; Okamura, M.; Schoepfer, R.; Rodowicz, T.
Abstract: LION is a laser ablation ion source to provide singly charged heavy ions of various species for RHIC-EBIS. High charge state heavy ion beams from RHIC-EBIS are used for RHIC physics experiments and NASA Space Radiation Laboratory (NSRL) quasi-simultaneously. The demands for heavy ion beams are growing and more ion species are available and more NSRL beam time is used because of unique capability and flexibility of the sources. With the combination of LION and RHIC-EBIS, ion species can be switched on a pulse-by-pulse basis without the effect of previously used species. The present performance and operation experiences of LION and RHIC-EBIS are shown.